Lack of Increased Hepatotoxicity in HIV-infected Pregnant Women Receiving Nevirapine Compared to Other Antiretrovirals - Ouyang, David W. (2010)
OBJECTIVE: To estimate whether HIV-infected pregnant women were at increased risk of hepatotoxicity when taking nevirapine (NVP) containing regimens compared to HIV-infected pregnant women taking antiretroviral therapy (ART) not containing NVP. METHODS: This analysis included HIV-infected pregnant women on ART from two multicenter, prospective cohorts: The Women and Infants Transmission Study (WITS) and the International Maternal Pediatric Adolescent AIDS Clinical Trials (IMPAACT) protocol P1025. Multivariate Cox proportional hazards regression models were used to investigate the association between NVP use and hepatotoxicity. NVP use was dichotomized as use or no use and further categorized according to ART exposure history. We investigated two outcomes: any liver enzyme elevation (LEE) (grade 1-4) and severe LEE (grade 3-4). RESULTS: A total of 1229 women with ART use during pregnancy were studied, 218 (17.7%) of whom received NVP. Among the women receiving NVP, 137 (62.8%) were NVP naïve. Twenty-nine women (13.3%) who received NVP developed any LEE and one (0.5%) developed severe LEE. Of the 1011 women on non-NVP regimens, 145 (14.3%) developed any LEE and 14 (1.4%) developed severe LEE. There were no maternal deaths. In univariate models, LEE was not significantly associated with CD4+ count > 250 cells/μL or NVP use. In adjusted multivariate models, no significant increased risk of LEE (any or severe) in women taking NVP was detected as compared to those taking other ART regardless of prior exposure history. CONCLUSIONS: We did not observe an increased risk of hepatotoxicity among HIV-infected pregnant women on NVP versus other ART, including women who were ART naïve.